Penerapan Model Role Playing dalam Pembelajaran IPS pada Materi Masyarakat yang Beradab Siswa Kelas IV - Krisnina, Krisnina; Pandra, Viktor; Frima, Aren (IJOCE: Indonesia Journal of Civic Education, 2024)
This study aims to determine the completeness of student learning outcomes after implementing the Role Playing Model in Social Studies Learning on Civilized Society Material for Class IV of SD Negeri 57 Lubuklinggau significantly. This type of research is Quantitative research. The approach used is pre-experimental designs with one group pretest-posttest design. Based on the analysis of the initial test results (pre-test) the average value is 42.43 and for the final test (post-test) the average value is 85.33. This shows that the average post-test value is greater than the average pre-test value. After being calculated using the Z-test formula, the Zcount value = 5.27 is obtained which is compared to the Ztable value with a significance level of 0.05 is 1.64. So the Zcount value = 5.27> Ztable = 1.64 indicates that Ha is accepted and Ho is rejected. In conclusion, the learning outcomes of students after implementing the role-playing model in Social Studies Learning on Civilized Society Material for Class IV of SD Negeri 57 Lubuklinggau are significantly complete. Keywords: Role Playing Model, Learning Outcomes, Social Studies